Masdevallia racemosa - Moreno, Juan Sebastián (2018)
Masdevallia racemosa, an endemic species from the Central Cordillera in Cauca department, is recognized by its long repent habit, with a creeping or ascending rhizome, a loose inflorescence of successive and simultaneous intense red-orange flowers, deeply connate sepals forming sepaline tube, elliptical acute petals and an oblong lip. Like other Masdevallia species with large, brightly-colored flowers, M. racemosa is commonly believed to be hummingbird pollinated. Nevertheless, the morphology of petals, lip and column, as can be seen in the LCDP, is consistent with fly pollination instead.